Hubungan Pengetahuan, Jarak Kehamilan, dan Paritas dengan Kejadian Kekurangan Energi Kronik (KEK) di Puskesmas Muara Burnai Kecamatan Lempuing Jaya Kabupaten Ogan Komering Ilir Tahun 2022 - Maulidina Humairoh; Siti Aisyah Hamid; Rizki Amalia (Universitas Batanghari Jambi, 2023)
KEK is a condition in which the mother is malnourished due to a chronic (chronic) deficiency of one or more dietary nutrients which results in relatively or absolute health problems for the mother. The factors that influence SEZ are socioeconomic factors, biological factors, consumption patterns and behavior. Socioeconomic factors consist of knowledge, occupation, family income, mother's education and marital status. Biological factors consist of the age of the pregnant woman, the distance between pregnancies and parity. The purpose of this study was to determine the relationship between knowledge, gestational distance, and parity simultaneously with the incidence of KEK in pregnant women in the working area of the Muara Burnai Health Center, Lemrub Jaya District, Ogan Komering Ilir Regency in 2022. The research design used in this study was an analytical survey with cross sectional design. The population in this study was the population in this study were pregnant women at the Muara Burnai Public Health Center, Lemembu Jaya District, Ogan Komering Ilir Regency who carried out pregnancy checks in December 2021 - January 2022. Based on the results of research using the chi-square statistical test, it was found that there was a significant relationship between knowledge and the incidence of KEK in pregnant women obtained p. value = 0.008, there is a significant relationship between the distance of pregnancy with the incidence of CED in pregnant women, obtained p. value = 0.000, there is a significant relationship between parity and the incidence of CED in pregnant women, obtained p. value = 0.002, it can be concluded that the relationship between knowledge, pregnancy distance, and parity in a partial or simultaneous manner to the incidence of KEK in pregnant women in the working area of the Muara Burnai Health Center, Lemembu Jaya District, Ogan Komering Ilir Regency in 2022. It is recommended for health workers at the Muara Burnai Health Center Lem debris Jaya District, Ogan Komering Ilir District, especially in the KIA poly, in order to increase education about the dangers of SEZ and how to overcome it to pregnant women, so that the incidence of SEZ can be reduced.Â